Essays in social anthropology - Chattopadhyay, K. P. (Kshitis Prasad), 1897-1963. (Calcutta : K.P. Bagchi & Co., 1994)
Study in Indian context.
Includes bibliographical references and index.
Keywords: Ethnology -- India; India -- Social life and customs